PENGARUH LITERASI DIGITAL TERHADAP KINERJA GURU - Ahyani, Nur; Fitria, Happy; Lian, Bukman; Nugroho, Hery Setio (STKIP PGRI Situbondo, 2024)
Teachers play an important role in improving the quality of education, especially in improving performance, therefore teachers need to understand and apply digital literacy so that students are encouraged to participate actively and innovatively, as well as create a fun learning environment. This research aims to determine and analyse the influence of digital literacy on teacher performance at SMA Negeri 3 Kayu Agung. This research is quantitative research using a survey method. This research was conducted at SMA Negeri 3 Kayu Agung with 79 teachers as respondents. Data collection techniques use questionnaires and documentation. Validity test uses construct validity and content validity. Meanwhile, the reliability test uses Cronbach’s Alpha. The data was analysed using descriptive data analysis techniques and non-parametric statistics, namely Spearman correlation. The research results show that there is an influence of digital literacy on the performance of high school teachers.